Evaluation of the rabbit as an experimental model for human uterine synechia - Mohamed Khrouf; Olivier Morel; Ali Hafiz; Pascale Chavatte-Palmer; Hervé Fernandez (Wolters Kluwer Medknow Publications, 2012)
Context: Pathogenesis of uterine synechia remains unsolved, the causal relationship between synechia and infertility is not clearly established. Aims: To evaluate the rabbit as an experimental model for Asherman's syndrome using the endometrial curettage as trigger mechanism then to evaluate its impact on fertility. Settings and Design: Experimental study Materials and Methods: 13 female rabbits. All submitted traumatic endometrial curettage. Animals of Group 1 (n = 7) were sacrificed at various times following surgery (day 7, 15 and 30), animals of Group 2 (n = 6) were bred and sacrificed during pregnancy. Main outcome were synechia occurring, number of implanted fetus, lumen surface/ global horn perimeter ratio (LS-GHP ratio) and epithelium thickness. Statistical Analysis: Means were compared using Student 't' test (P < 0.05 was considered significant). Number of implantation sites of two horns were compared with the Wilcoxon test. Results: No synechia have been observed. Examinations at Day 7, 15 and 30 demonstrate a complete regeneration of endometrium. We observed a significant diminished LS-GHP ratio at day 7 (0.042 ± 0.004 vs 0.074 ± 0.002 mm; P = 0.013) with a higher simple columnar epithelium compared to control (16.6 ± 3.39 vs 10.98 ± 1.7; P = 0.001). We observed a diminished ovum implantation in traumatized horns, even if it was not statistically significant. Conclusion: Even if no intrauterine adhesion were observed, this model represents a pathogenesis condition in the rabbit similar to intrauterine adhesions observed in the human with negative impact on implantation.